Prognostic role of tumor-infiltrating lymphocytes in gastric cancer: A systematic review and meta-analysis. Issue 32 (August 2018) - Lee, Jung Soo; Won, Hye Sung; Sun, Der Sheng; Hong, Ji Hyung; Ko, Yoon Ho
Abstract: Background: The potential prognostic value of tumor-infiltrating lymphocytes (TILs) in gastric cancer remains controversial. This meta-analysis examines the association between TILs and survival outcomes in gastric cancer. Methods: Twenty-two eligible studies were identified using the PubMed and Google Scholar databases. The combined sample size of the 22 studies was 2941, and the median sample size of the individual studies was 122 patients (52–220). The main clinical outcomes examined were overall cancer survival (OCS) and overall cancer relapse-free survival (OCRFS). Results: Tumor tissue CD3(+) TILs, indicative of pan-T-cell expression, had a positive effect on survival with a hazard ratio (HR) of 0.64 (95% confidence interval [CI] 0.52–0.78) for OCS, as did the non-FOXP3(+) T-cell subgroup with an HR of 0.66 (95% CI 0.57–0.75), particularly in CD8(+) lymphocytes (HR = 0.63, 95% CI 0.48–0.83). On the contrary, high FOXP3(+) T-cell expression was correlated with reduced OCS, with an HR of 1.75 (95% CI 1.26–2.42). Analysis of the seven studies evaluating OCRFS revealed improved OCRFS with infiltration of non-FOXP3(+) TILs with an HR of 0.59 (95% CI 0.42–0.81) but not FOXP3(+) T lymphocytes with an HR of 1.82 (95% CI 1.30–2.53). Conclusion: The results from this meta-analysis suggest that high expression of TILs, mainly by CD8 lymphocytes, may be a potential prognostic biomarker in patients with gastric cancer. Abstract : Supplemental Digital Content is available in the text